The rise of targeted HIV oral rapid testing in Australia. Issue 5 (9th March 2015) - Chan, Derek; Stewart, Michael; Smith, Maggie; Price, Tony; Lusk, Jo; Ooi, Catriona; Read, Phillip; Finlayson, Robert
Abstract: Objective: To assess the performance and acceptability of the OraQuick Advance Rapid HIV‐1/2 Antibody Test (ORT) in Australia. Design, p articipants and s etting: Cross‐sectional study of 1074 men who have sex with men (MSM) and individuals aged 18 years or older at high risk of acquiring HIV infection who attended five public HIV or sexual health services, two general practices and one community clinic in Sydney from 1 January to 31 December 2013. Intervention: One ORT confirmed by fourth‐generation HIV enzyme immunoassay (EIA). Main outcome measures: ORT sensitivity and specificity compared with EIA; acceptabiity of the ORT to participants. Results: 83.5% of participants were MSM, 90.3% were aged under 50 years, and 9% had never been tested for HIV. There were 11 true‐positive ORT results, two false‐negative (non‐reactive) results (both were early infections), and one false‐positive (reactive) result (due to reader error). Sensitivity and specificity were 84.6% and 99.8%, respectively (compared with a sensitivity of 99.3% and specificity of 99.8% listed by the manufacturer). Three quarters of participants (74.0%; 730/987) found the ORT less stressful than venous sampling. Those who usually had tests at intervals of greater than 3 months deemed the ORT less stressful than those who had quarterly tests (77.5% v 64.8%; P  < 0.001). Nearly all participants (99.2%; 998/1006) would have an ORT again and 99.4% (994/1000) would recommend it to peers. Most participants (69.1%; 720/1042) felt ORT approval by Australia's Therapeutic Goods Administration (TGA) would encourage testing. Conclusion: ORT sensitivity is reduced in early HIV infection. The test is highly acceptable and less stressful than venous sampling. Participants are keen to be tested with the ORT in future, would recommend it to peers and would have tests more frequently if the ORT were licensed. TGA approval of this test might slow increasing HIV infection rates among MSM and others by facilitating diagnosis and treatment.